(3GdUdhGJ GdTQjaIs - (3GdgeOGfj, GdcGXej, EeGe GdMQejf, eMeO Hf YHO GdhgGH Hf OGhO, J (B1305(3g`s ((3eMeO SejYs)
(3ChdgG (B:s
(3GdMeO ddg GdPj bQf HGdUdhGJ fLM OYhGJ GdHTQ(B... (3CeG HYO aMOKfG KbI fbI eef CNdU dfG GdebI, bGd hQOfG GdYQGb(B...s
(3BNQgG (B:s
(3hdG PQjI EdG SHjJgG hdG YGajI EdG RhjJgG Efc Ydi Pdc bOjQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B472s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs